The rate of cooling of the pulsating white dwarf star G117-B15A: A new asteroseismological inference of the axion mass - Córsico, Alejandro Hugo (2012)
We employ a state-of-the-art asteroseismological model of G117-B15A, the archetype of the H-rich atmosphere (DA) white dwarf pulsators (also known as DAV or ZZ Ceti variables), and use the most recently measured value of the rate of period change for the dominant mode of this pulsating star to derive a new constraint on the mass of axion, the still conjectural non-baryonic particle considered as a candidate for dark matter of the Universe. Assuming that G117-B15A is truly represented by our asteroseismological model, and, in particular, that the period of the dominant mode is associated with a pulsation g mode trapped in the H envelope, we find strong indications of the existence of extra cooling in this star, compatible with emission of axions of mass macos2β=17.4-2.7+2.3 meV.